Harnessing Traditional Knowledge for Circular Livestock, Environmental Resilience and Its Perspectives from Odisha, India - Das, Abhijeet; Mishra, Satchidananda (New Countryside, 2025)
The article explores the role of traditional knowledge systems (TKS) in creating circular livestock economies and fostering environmental stewardship. The study focuses on Pathe Pathshala, a mobile, community-led education initiative led by grassroots veterinarian Dr. Balaram Sahu, and shows how locally embedded practices in animal care, ethno-veterinary medicine, and adaptive breeding can serve as resilient and regenerative alternatives to industrial livestock production. The research challenges established development discourses by highlighting decentralised, low-input, and ecologically integrated animal husbandry practices based on community knowledge. The research investigates how such approaches improve occupational safety for herders, safeguard animal health, and provide long-term livelihoods, especially for marginalised rural people. The study, which is theoretically inspired by agroecology, post-development pedagogy, and environmental justice, makes the case that indigenous livestock systems are active epistemologies capable of informing regenerative transitions rather than cultural relics. It advocates for a rethinking of livestock policy and agricultural education in the Global South, emphasising the need to incorporate indigenous values and place-based innovations into larger circular economy frameworks. By providing empirical insights into an under-represented subject, the research adds to critical discussions about sustainability, knowledge diversity, and the future of rural transformation, transcending technocratic paradigms.